Religion, Education, Security - Gearon, Liam 1962- (2019)
On first glance the politicization and securitization of religion may seem remote from education. A second look reveals widespread international initiatives aimed at the uses of education precisely for political and security purposes, notably in the countering of terrorism, violent extremism and ideologies opposed to liberal democratic values. This editorial presents a critical framing on how scholars from a range of interrelated disciplines analyze the interface of religion, education and security. The purpose of this Special Issue is thus critically to engage scholars across religious studies and theology, politics and international relations, security and intelligence studies, to explore through empirical evidence and reasoned argument the role here for religion in education. The volume aims to make some ground-breaking cross-disciplinary theoretical advances and methodological innovations not simply to further debate but to provide the tools for asking new questions and opening new pathways and frameworks for exploring the critical interface of religion, education and security.
Keywords: Counter-terrorism; Education; intelligence studies; Political Theology; Religion; Security; security studies; Terrorism